2018
DOI: 10.7196/samj.2018.v108i5.12802
|View full text |Cite
|
Sign up to set email alerts
|

The costs and outcomes of paediatric tuberculosis treatment at primary healthcare clinics in Johannesburg, South Africa

Abstract: These results are the first reported estimates of paediatric DS-TB treatment costs in SA and show the potential cost savings of closer adherence to national treatment guidelines. The findings were robust in sensitivity analyses and are lower than previous cost estimates in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
3
8
2
Order By: Relevance
“…It is possible some extrapulmonary TB cases may have been misdiagnosed. The commonest extrapulmonary Tb found was TB adenitis, which is also similar to the report of a previous study [7].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is possible some extrapulmonary TB cases may have been misdiagnosed. The commonest extrapulmonary Tb found was TB adenitis, which is also similar to the report of a previous study [7].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are similar with those of Affusim et al [6] who reported that 78.6% of the TB cases found were pulmonary TB and extrapulmonary TB accounted for 21.4%. It is also similar to the 92% pulmonary TB reported by Budgell et al [7]. Though Ogbudebe et al [8] also found more pulmonary TB compared to extrapulmonary TB, the proportion of their pulmonary TB was quite low (58.0%) compared to ours and their extra pulmonary TB was much higher (42%) than ours.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…HIV co-infection is said to be the most powerful risk factor for progression from TB infection to active disease due to progressive weakening of the immune system [13].This study revealed a TB/HIV co-infection rate of 35%, which is higher than the 14.9%, 29% and 22.7% in three previous studies in Nigeria [6] [14] and South Africa [15]. Rivers State was the state with the highest HIV prevalence (15.2%) in 2012 (the period under consideration in this study) and states in South West Nigeria had very low prevalence rates, ranging from 0.2% to 4.3% [16].…”
Section: Discussionmentioning
confidence: 62%